2021
DOI: 10.1039/d1tc01989a
|View full text |Cite
|
Sign up to set email alerts
|

Mechanically tunable magnetic and electronic transport properties of flexible magnetic films and their heterostructures for spintronics

Abstract: The incorporation of flexible conception into spintronics has attracted long-standing scientific attention because the contemporary consumer electronic devices compared with conventional silicon-based counterparts urgently needs spintronic devices can be shaped...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 171 publications
0
11
0
Order By: Relevance
“…Mechanical bending is the most common way employed in literature to actively control the strain in oxide thin film. [ 141 ] Two main types of strategies were developed: 1) bending of layers supported on a flexible or curved substrate (Figure 7c) and 2) bending of self‐standing thin films (Figure 7d). In both cases, bending generates an in‐plane strain, εx${\varepsilon _x}$, along the bending direction proportional to the distance, b i , from the neutral plane: εxbadbreak=βR\begin{equation} {\rm{\;}}{\varepsilon _x} = \frac{\beta }{R} \end{equation}where R is the radius of curvature of neutral plane.…”
Section: Strain Control In Freestanding Perovskite Oxide Thin Filmsmentioning
confidence: 99%
“…Mechanical bending is the most common way employed in literature to actively control the strain in oxide thin film. [ 141 ] Two main types of strategies were developed: 1) bending of layers supported on a flexible or curved substrate (Figure 7c) and 2) bending of self‐standing thin films (Figure 7d). In both cases, bending generates an in‐plane strain, εx${\varepsilon _x}$, along the bending direction proportional to the distance, b i , from the neutral plane: εxbadbreak=βR\begin{equation} {\rm{\;}}{\varepsilon _x} = \frac{\beta }{R} \end{equation}where R is the radius of curvature of neutral plane.…”
Section: Strain Control In Freestanding Perovskite Oxide Thin Filmsmentioning
confidence: 99%
“…Instead of polymer films, rigid substrates such as silicon wafers and glasses can also become flexible by decreasing their thickness to a micrometer range. For example, Pérez et al reported the flexible GMR sensors on an ultrathin silicon substrate with thicknesses of 100 and 50 μm . As presented in Figure (B1), the fabrication process started with the deposition of GMR multilayers on silicon wafers, followed by a grinding process from the backsides of the wafers to reduce the thickness to 100 or 50 μm.…”
Section: Overview Of Different Types Of Gmr Sensorsmentioning
confidence: 99%
“…For example, topological insulators are natural candidates for low-power spintronics because of their intrinsic dissipationless feature. It is possible, for example, to combine the mechanical strain and the giant magnetoresistance of a ferromagnet junction of the topological insulator to construct a novel straintronics device with a robust strain-controllable magnetic switch [ 168 ], and even tune magnetic and electronic properties mechanically [ 169 ]. These recent studies of strain-sensitive giant magnetoresistance responses, along with other phenomena, have indicated that these types of devices have a great potential for low-power nanoscale strain sensors and other sensing applications.…”
Section: Mathematical and Computational Models For Smart Materials An...mentioning
confidence: 99%